THE CULTURE OF INFANT CARE BY TRAINER BIRTH ATTENDANT IN DAMPIT, MALANG - Wandi Wandi (Indonesian Midwifery and Health Sciences Journal, 2022)
This study was conducted to describe the culture of infant care by TBA in Dampit District Malang Regency. The research design uses qualitative research design with case study type. Data collection techniques used interviews, observation, documentation and focus group discussions. Informant consist of TBA, midwife and baby family. The sampling technique used is purposive sampling. Validity test and criteria used include source triangulation and method triangulation. After that the data is analyzed by using thematic analysis technique and content analysis. The results showed that the period of infant care performed by the TBA was carried out since the infant was taken home from midwife to the age of 36 days. If the umbilical cord has not been taken a care of every morning and evening. People still believe that the placenta is a baby brother so that the burial should be done well according to the culture of the community. Baby massage is done from newborn to 36 days with the procedure according to the culture is society. Bathing the baby is done by the midwife when the new baby comes home from the midwife except the infant who has not received permission to be bathed from the health worker. There are bathed morning and evening but there is also bathed in the morning only. Cord care is performed twice a day. In the treatment there are with bethadin, alcohol, dry gauze and there are still smeared with betel leaf and salt. Shaved babies performed by TBA when he was over 5 days, after shaved smeared with katuk leaves. Since the role of TBA in the community is still considerable, the guidance by health workers must be done. Keywords : Infant care , Trainer Birth Attendant